Load Capacity of Curved-up Beams - Youkhanna, Kanaan (European Scientific Journal, ESJ, 2023)
Straight and curved-up beams are cast as part of portal frame models. The models are made as single-span, double-span, and triple-span models. Experimental investigation is conducted to predict load capacity of curved-up beams compared to straight beams. Load was applied onsite using traditional load application. The enhancement of load capacity of a curved-up beam compared to straight beam is predicted. The enhancement in load capacity is predicted for single-span, double-span, and triple-span portal frame models is presented.